(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
“There have been many Mahatmas in India whose sole objectwas to remove Untouchability and to elevate and absorb the Depressed Classes,but every one of them has failed in his mission. Mahatmas have come andMahatmas have gone. But the Untouchables have remained as Untouchables.”